Hemoglobin level in elite speed skaters from 2000 up to 2005, and its relationship with competitive results - Kuipers, H.; Moran, J.; Dubravcic-Simunjak, S.; Mitchell, D. W.; Shobe, J.; Sakai, H.; Ambartsumov, R. (International Journal of Sports Medicine, 2007)
We studied the mean hemoglobin (Hb) concentration in elite male and female long track junior and senior speed skaters from 2000 to 2005. In addition, the number of abnormal hematological findings observed over this period of time was investigated. We also studied whether there were differences in Hb concentration between top ranked and lower ranked skaters, and whether a relationship between Hb concentration and competitive results could be observed. The present study shows that the mean Hb level in male and female junior and senior long track speed skaters remained fairly stable and did not change from 2000 through 2005. The number and percentage of abnormal hematological findings were found to vary between 0 and 2 %, and failed to show a clear pattern or trend over the years. There was no difference in mean Hb levels between top ranked and lower ranked skaters, and no meaningful relationship between Hb concentration and ranking could be found.